Phylogenetic patterns suggest frequent multiple origins of secondary metabolites across the seed-plant 'tree of life'. Issue 4 (21st May 2020) - Zhang, Yongzeng; Deng, Tao; Sun, Lu; Landis, Jacob B; Moore, Michael J; Wang, Hengchang; Wang, Yuehua; Hao, Xiaojiang; Chen, Jijun; Li, Shenghong; Xu, Maonian; Puno, Pema-Tenzin; et al.
Abstract: To evaluate the phylogenetic patterns of the distribution and evolution of plant secondary metabolites (PSMs), we selected 8 classes of PSMs and mapped them onto an updated phylogenetic tree including 437 families of seed plants. A significant phylogenetic signal was detected in 17 of the 18 tested seed-plant clades for at least 1 of the 8 PSM classes using the D statistic. The phylogenetic signal, nevertheless, indicated weak clustering of PSMs compared to a random distribution across all seed plants. The observed signal suggests strong diversifying selection during seed-plant evolution and/or relatively weak evolutionary constraints on the evolution of PSMs. In the survey of the current phylogenetic distributions of PSMs, we found that multiple origins of PSM biosynthesis due to external selective forces for diverse genetic pathways may have played important roles. In contrast, a single origin of PSMs seems rather uncommon. The distribution patterns for PSMs observed in this study may also be useful in the search for natural compounds for medicinal purposes.